The Role of Herbal Medicine in Combating Chronic Diseases: Mechanisms and Therapeutic Potential - Ebadi, Abdol Ghaffar (International Journal of Human and Health Sciences (IJHHS), 2025)
Chronic illnesses like cardiovascular disease, diabetes, cancer, and neurodegenerative diseases have emerged as major global health concerns, responsible for high rates of morbidity and mortality. With an increase in the healthcare burden, interest has developed in complementary and alternative therapies, one of which has been herbal medicine. Herbal medicines, derived from a vast array of plants, contain bioactive molecules that have shown promise in the prevention and treatment of chronic diseases. The review explains how herbal medicines perform their therapeutic roles via antioxidant, anti-inflammatory, and immunomodulatory activities. It also explains the molecular mechanisms behind the efficacy of herbal medicines, including gene expression and enzyme modulation. The therapeutic potential of various herbs in the management of chronic diseases such as hypertension, diabetes, cancer, and arthritis is discussed, with clinical evidence supporting their use. Despite the promising findings, concerns regarding lack of standardization, toxicity, and herbdrug interactions remain paramount. The future direction must be to resolve these concerns through definitive clinical trials, improving quality control, and the integration of herbal medicine into conventional health systems. Herbal medicines, in general, are a valuable resource for the therapy of chronic diseases, and their therapeutic usefulness is far from being depleted. International Journal of Human and Health Sciences Vol. 09 No. 02 Apr’25 Page: 75-85